Nanostructured Didymosphenia Geminata-Based Membrane for Efficient Lead Adsorption from Aqueous Solution - Garcia-Herrera, C; Cabezas-Cornejo, R (Elsevier Ltd, 2021)
The need for new technologies more efficient and less expensive to remove heavy metals from aqueous environments has lead to the development of novel biosorption-based membranes, where the adsorbent agent has a biological origin. In this work we propose the use of the biopolymer from a highly invasive microalgae, Didymosphenia geminata or Didymo, as lead adsorbent in a nanostructured membrane designed to facilitate heavy metal removal applications. Nanofibrilated cellulose was used as a membrane matrix, due to its non-toxic nature and good reinforcement abilities. In addition multi-walled carbon nanotubes (CNTs) were introduced into the membrane to improve structural and antifouling performance, which are critical aspects for membrane applications. The kinetics and nature of the adsorption process of the membrane were evaluated, confirming a high lead adsorption capacity (129 mg g-1), when compared to other biopolymers from micro and macroalgae. According to our measurements, this adsorption is connected to the presence of sulphur-based functional groups in the Didymo biopolymer. When CNTs are added to the membrane its adsorption capacity increases, probably due to an increment of the membrane porosity and molecular diffusion. Antifouling and mechanical properties of the Didymo-based membranes were also explored. Phylogenetic studies confirmed the presence of only one genetic lineage of D. geminata found in all locations affected by this plague in Chile. The availability of biopolymer in the region with reproducible lead adsorption results increases the potential applicability of this biomaterial by adding value to a species well-known for having negative impacts on ecosystems and human activities. © 2021 Elsevier Ltd.